Effectivity of interactive multimedia with theocentric approach to the analytical thinking skills of elementary school students in science learning - Azmil Hasan Lubis; Febrianawati Yusup; Muhammad Darwis Dasopang; Sapitri Januariyansah (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2021)
This study aims to analyze the effectivity of interactive multimedia with the theocentric approach on the analytical thinking skills of elementary school students in science learning. This study used a quantitative approach with a quasi-experimental type. The sampling technique used cluster random sampling with 67 students. The data were collected through analytical thinking skills tests given before and after science learning. The data analysis technique used descriptive and inferential statistics analysis by comparing the increase in the average results of the test and t-test. The research results show that the increase of the average value of students' analytical thinking skills in the experimental class is higher, which is an increase of 44.74% compared to the control class which only increases by 17.20%. The results of the t-test also show that there is a significant effect between interactive multimedia with theocentric approach on students' analytical thinking skills with a significance value of 0.00 (<0.05). Therefore, interactive multimedia with the theocentric approach is effectively used to improve the analytical thinking skills of elementary school students in science learning.